Extraction of ochratoxin A in bread samples by the QuEChERS methodology - Paíga, Paula (2013)
A QuEChERS method for the extraction of ochratoxin A (OTA) from bread samples was evaluated. A factorial design (23) was used to find the optimal QuEChERS parameters (extraction time, extraction solvent volume and sample mass). Extracts were analysed by LC with fluorescence detection. The optimal extraction conditions were: 5 g of sample, 15 mL of acetonitrile and 3 min of agitation. The extraction procedure was validated by systematic recovery experiments at three levels. The recoveries obtained ranged from 94.8% (at 1.0 μg kg -1) to 96.6% (at 3.0 μg kg -1). The limit of quantification of the method was 0.05 μg kg -1. The optimised procedure was applied to 20 samples of different bread types (‘‘Carcaça’’, ‘‘Broa de Milho’’, and ‘‘Broa de Avintes’’) highly consumed in Portugal. None of the samples exceeded the established European legal limit of 3 μg kg -1.